Budgetary responses to COVID-19: the case of South Korea. Issue 5 (21st September 2020) - Kim, Bong Hwan
Abstract : Purpose: This paper presents the details, circumstances and issues relating to Korea's budgetary responses to COVID-19. Design/methodology/approach: The author analyzes the details and consequences of budget responses to COVID-19 of Korea. Findings: Korea has implemented two supplementary budgets, worth 50 tn KRW, which were approved by the National Parliament within an average of 13 days. This was an exceptionally quick approval by the Parliament. While these prompt actions help the government provide necessary measures to combat the pandemic, hasty decisions may have long-term consequences on fiscal soundness. Effective handling of COVID-19 in Korea increased the approval rating for the current administration. Originality/value: This is consistent with the argument by Bartels (2013) who states that ordinary citizens assess politicians and policies primarily on the basis of visible evidence of success or failure. Because evaluations on government projects other than handling crisis is out of people's interests during pandemic, inefficient projects tend to be maintained. For future, it is desirable to have a fiscal rule beforehand to address a crisis.